THE SUBTITLING STRATEGIES OF CULTURE-RELATED TERMS IN KISAH TANAH JAWA: MERAPI (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
The audiences' need for subtitles has increased as the interest in global streaming platforms has skyrocketed. Understanding the Source Language (SL) and subtitling strategies is required to produce an equivalent subtitle of a culture's expressions in the Target Language (TL), notably in the subtitling of terms related to Javanese and Indonesian culture. Moreover, culture-related terms are part of a group's identity, as to why the problems of this topic are challenging, therefore, worth researching. Besides, there are several things to be considered in making subtitles to help build a better understanding of the plot, such as the speaker's screen duration. Thus, this study aims to analyze the types of subtitling strategies used in Iflix's original series Kisah Tanah Jawa: Merapi (KTJ). Furthermore, descriptive qualitative methods and textual analysis approaches are used to analyze the data, which require in-depth data analysis. As for the data collection, it applied observation and library research. The object is examined utilizing reputable sources to disclose its respective types of cultural terms and subtitling strategies. Based on the cultural terms classified by Newmark plus Tomalin and Stempleski, the research reveals the terms in the KTJ series, which are divided into seven categories, namely beliefs, institutions, customs, art, ecology, religious terms, and foods. By using Gottlieb's theory on subtitling strategies, six types of strategies are found in the data. It includes transfer, imitation, expansion, paraphrase, condensation, and decimation, with transfer being the most dominant strategy.